MEMAHAMI DIRI DAN DUNIA: PENDEKATAN ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI DALAM REALITAS HARIAN - Erlangga Akhazi; A Kholibi, Rendi Septian, Siti Mubadi Awaliyah, Andi Rosa (CV. Adiba Aisha Amira, 2025)
This article explores how humans understand themselves and the world through the main approaches in philosophy, namely ontology, epistemology, and axiology. Ontology plays a role in revealing the essence of human existence and the fundamental nature of the reality that surrounds it, helping to answer fundamental questions about who we are and how the world is structured. Epistemology presents perspectives on the human process of acquiring and forming knowledge, whether through empirical experience, logical thinking, or inner reflection. On the other hand, axiology highlights the aspect of value, examining how humans determine the meaning of life, distinguish between good and bad, and make values the basis for action in everyday life. By combining these three approaches, this article aims to present a comprehensive picture of the relationship between humans and the world, as well as demonstrate how philosophical thinking can be applied in the dynamics of daily life, from decision-making to the search for meaning in life